2010
DOI: 10.1111/j.1440-1746.2010.06417.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR‐221 directly amplified from plasma is a potential diagnostic and prognostic marker of colorectal cancer and is correlated with p53 expression

Abstract: The direct amplification of plasma miR-221 can be used as a potential noninvasive molecular marker for diagnosis and prognosis of CRC and is correlated with p53 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(203 citation statements)
references
References 43 publications
9
192
0
2
Order By: Relevance
“…In these studies, miR-221 and miR-21 were upregulated in the plasma of CRC patients compared to healthy controls [79,83] , while miR-601 and miR-760 were down-regulated [78] . Moreover, a study conducted in two independent CRC cohorts suggested that high levels of plasma miR-141 could predict poor survival, and thus miR-141 may serve as an independent prognostic factor for advanced CRC patients [81] .…”
Section: Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, miR-221 and miR-21 were upregulated in the plasma of CRC patients compared to healthy controls [79,83] , while miR-601 and miR-760 were down-regulated [78] . Moreover, a study conducted in two independent CRC cohorts suggested that high levels of plasma miR-141 could predict poor survival, and thus miR-141 may serve as an independent prognostic factor for advanced CRC patients [81] .…”
Section: Markersmentioning
confidence: 99%
“…Many studies have been performed to quantify miRNAs in the blood for use as a biomarker (Table 4) [77][78][79][80][81][82][83][84][85][86][87][88] . miR-92a, located on chromosome 13q13, is a member of the miR-17-92 gene cluster.…”
Section: Mirna Biomarkers In Bloodmentioning
confidence: 99%
“…miR-221 has been reported to be over-expressed in many human tumor tissues, such as breast cancer (81), colorectal cancer (80), glioblastoma (82) and prostate cancer (83). A recent report shows that miR-221 stimulates the onset of tumors and promotes tumor progression, significantly shortening the mean time to death in a mouse model of liver cancer (84).…”
Section: Mirnas Up-regulated In Hcc 321 Mir-221mentioning
confidence: 99%
“…Using microarray analysis, Shimizu et al found that let-7 miRNAs negatively regulate B-cell lymphoma 2 like protein 1 (Bcl-Xl) expression and can induce apoptosis when used with an anti-cancer drug targeting myeloid cell leukemia sequence 1 (Mcl-1) in human HCC (79). It's identified that let-7g may partially suppress HCC metastasis through targeting collagen, type I, alpha 2 (COL1A2) (80). The various functions of the let-7 miRNA family involved in DNA replication, apoptosis and cellular differentiation create a collaborative inhibitive effect against HCC development.…”
Section: Let-7 Familymentioning
confidence: 99%
“…serum and plasma) and demonstrated that the levels of certain miRNAs were altered in response to various malignancies (Chim et al 2008, Lawrie et al 2008, Mitchell et al 2008, raising the exciting possibility of using blood-based miRNA testing to assist in disease detection and management. Since those seminal papers, the utility of cell-free miRNAs as biomarkers of cancer has become increasingly apparent in preclinical studies: serum or plasma miRNAs have been used for cancer diagnosis and staging , Liu et al 2010, Pu et al 2010, Roth et al 2010, prognosis (survival or relapse; Pu et al 2010, Liu et al 2011, and predicting response to therapy (Zhang et al 2010a). More recently, miRNAs have been isolated in many other body fluids, including urine, saliva, semen, tears, breast milk, and amniotic fluids, suggesting that their release or export occurs from most tissue and cell types (Hanke et al 2009, Park et al 2009.…”
Section: Mirnas As Biomarkers Of Malignancymentioning
confidence: 99%